2021
DOI: 10.1177/1550059421991710
|View full text |Cite
|
Sign up to set email alerts
|

Salzburg Criteria, A Useful Tool in Non-Convulsive Status Epilepticus Diagnosis: A Retrospective Study

Abstract: Introduction. Non-convulsive status epilepticus (NCSE) has been traditionally a challenging electroencephalographic (EEG) diagnosis. For this reason, Salzburg consensus criteria (SCC) have been proposed to facilitate correct diagnosis. Methods. We retrospectively reanalyzed 41 cases referred to our department (from 2016 to 2018) under the suspicion of NCSE. In this study, we compared the original description (standard criteria) versus the updated description (SCC) of the same EEG. Results. Originally, 15 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(33 reference statements)
0
2
0
1
Order By: Relevance
“…Horvath et al reported that NCSE was associated with mortality during long-term follow-up (odds ratio 9.86) [29]. Additionally, Dominguez et al reported that worse outcomes were observed in patients with NCSE who had been overlooked and had not been treated properly [30]. In addition to these clinical studies, one preclinical study supports the poor outcomes of NCSE by demonstrating histological neural damage and glial reactive changes caused by NCSE using rodent models [31].…”
Section: Discussionmentioning
confidence: 99%
“…Horvath et al reported that NCSE was associated with mortality during long-term follow-up (odds ratio 9.86) [29]. Additionally, Dominguez et al reported that worse outcomes were observed in patients with NCSE who had been overlooked and had not been treated properly [30]. In addition to these clinical studies, one preclinical study supports the poor outcomes of NCSE by demonstrating histological neural damage and glial reactive changes caused by NCSE using rodent models [31].…”
Section: Discussionmentioning
confidence: 99%
“…Gómez Domínguez und Kollegen validierten die Salzburgkriterien im direkten Vergleich mit den zuvor verwendeten Standard-Kriterien zur NCSE-Diagnostik anhand von 41 Patienten. Eine Auswertung von Sensitivität und Spezifi tät erfolgte im Rahmen der durchgeführten Analysen nicht, allerdings erfüllten 14 der 26 initial als nicht-NCSE-verdächtig gewerteten Fälle gemäß der Salzburg-Kriterien die Diagnosekriterien eines möglichen NCSE [ 20 ] .…”
Section: ▪ Verschlechterung Des Klinischen Zustands Innerhalb Vonunclassified
“…The criteria 54 , 55 state that either epileptiform discharges (EDs) or rhythmic delta activity (RDA) needs to be present to diagnose NCSE during 10 s at least. Depending on the frequencies shown in EDs or RDA, two ways to proceed with the diagnosis are presented:…”
Section: Nonconvulsive Sementioning
confidence: 99%